2020
DOI: 10.1038/s41419-020-02896-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TTN-AS1 promotes the progression of cholangiocarcinoma via the miR-320a/neuropilin-1 axis

Abstract: Neuropilin-1 regulated by miR-320a participates in the progression of cholangiocarcinoma by serving as a co-receptor that activates multiple signaling pathways. The present study sought to investigate upstream lncRNAs that control the expression of miR-320a/neuropilin-1 axis and dissect some of the underlying mechanisms. Here we report lncRNA TTN-AS1 (titin-antisense RNA1) acts as a sponging ceRNA to downregulate miR-320a and is highly expressed in human cholangiocarcinoma tissues and cells. The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
2
31
1
Order By: Relevance
“…Moreover, the association of NRP-1 and CCA development has been confirmed by NRP-1 knockdown leading to impaired cancer cell proliferation, blocked cell cycle, reduced cell migration, and reduced focal adhesion kinase expression[ 105 ]. In line with that finding, NRP-1 overexpression in intrahepatic CCA cells that was associated with miR-320a downregulation boosted cell proliferation and epithelial to mesenchymal transition and stimulated tumor angiogenesis[ 106 ]. Recently, high NRP-1 expression was correlated with poor prognosis and reduced overall survival of intrahepatic CCA patients[ 107 ].…”
Section: Liver Cancersupporting
confidence: 61%
“…Moreover, the association of NRP-1 and CCA development has been confirmed by NRP-1 knockdown leading to impaired cancer cell proliferation, blocked cell cycle, reduced cell migration, and reduced focal adhesion kinase expression[ 105 ]. In line with that finding, NRP-1 overexpression in intrahepatic CCA cells that was associated with miR-320a downregulation boosted cell proliferation and epithelial to mesenchymal transition and stimulated tumor angiogenesis[ 106 ]. Recently, high NRP-1 expression was correlated with poor prognosis and reduced overall survival of intrahepatic CCA patients[ 107 ].…”
Section: Liver Cancersupporting
confidence: 61%
“…We performed integrated RNA-seq and proteomic analyses and found that AGO2 knockdown led to the upregulation of NRP1, not only at the mRNA level but also at the protein level in multiple CRC cells. NRP1 is well recognized as a key molecule in the process of cancer invasion and metastasis, and its overexpression has been detected in various metastatic tumors 35 , 36 , 40 . Importantly, EMT in CRC might be NRP1-dependent 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation and epigenetic modification are two significant mechanisms that control miRNA expression [ 57 , 64 , 100 , 101 ]. As the miR-320 family acts as a tumor repressor has attracted increasing interest in many human tumors, and transforming the tumor suppression signal from miR-320 may be a new strategy to treat cancers in the future.…”
Section: Regulation Of Mir-320 Expressionmentioning
confidence: 99%
“…The regulation mechanisms for miR-320 expression have been studied in several cell types, and some pivotal TFs were demonstrated to be relevant to this process. A recent study reported that lncRNA TTN-AS1 was able to downregulate hsa-miR-320a-3p through post-transcriptional regulation in cholangiocarcinoma cells, which depended on the Ago2 pathway [ 64 ]. E2A can realize self-regulation as a transcription factor in the process of accelerating the disease progression of CRC cells [ 101 ].…”
Section: Regulation Of Mir-320 Expressionmentioning
confidence: 99%